Or, on being the other woman - White, Simone, 1972- (Duke University Press, 2022)
"Simone White's or, on being the other woman is a book-length poem that considers the dynamics of contemporary Black feminist materiality. White writes through a hybrid of poetry, essay, personal narrative, and critical theory in order to attest to the narrative complexities of writing and living as a Black woman and artist"--